Optimizing Coastal Management: A Comprehensive Value Chain Analysis Approach for Sustainable Economic Development in Java, Indonesia - Rozaki, Zuhud; Ariffin, Ahmad Shabudin; Ramli, Mona Fairuz; Nurrohma, Elvina; Ramadhani, Novara Nurvinka; Setyoasih, Winda Ismah; Senge, Masateru (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract Coastal areas have become an important part of Indonesia's evolving economy, with a variety of commercial activities taking place. The island of Java has both northern and southern coastal areas, each with its own distinctive characteristics and products. The studies about coastal development through its product value chain are still limited. This study aimed to determine the value chain of fishery products in Java to provide recommendations for enhancing coastal management. For the northern coast, milkfish and ariid catfish from Juwana Coast (Pati Regency, Central Java) were selected, while Whiteleg Shrimp from Mendit Coast and Trisik Coast of Kulon Progo Regency, Yogyakarta were chosen to represent the southern coast. The study involved 48 respondents, including small and medium-sized enterprises (SMEs), farmers, fishermen, wholesalers, middlemen, retailers, restaurants, and consumers. The analysis techniques used in this study included Porter's value chain, Hayami's added value, Return/Cost (R/C) Ratio, and marketing margin analysis. The results of the study revealed that the products followed various channels in the value chain, with longer chains leading to higher prices for the end consumers. The findings also indicated that processed and creatively packaged products tend to command higher prices and generate greater profits. Coastal management should not only focus on upstream activities but also consider downstream processes to increase the value of coastal products. Efforts to enhance coastal management should consider key actors and government interventions through developing the coastal local products. Highlight Research The coastal area of Java Island makes a significant contribution to the local economy. The supply chain of Whiteleg Shrimp, Ariid Catfish, and Milkfish involves various actors who play important roles in maintaining the distribution of coastal products. Value chain analysis reveals opportunities to increase and improve the quality of products to enhance their worth. It is necessary to enhance coastal management by involving local institutions, the government, and the private sector.